Batf3-cDC1 control Th1 and fungicidal responses during cryptococcal meningitis: is this enough to control meningitis? - Carolina Coelho (mBio)
ABSTRACT Dendritic cells are crucial for bridging innate and adaptive immunity. Cryptococcosis, caused by Cryptococcus neoformans and Cryptococcus gattii, is responsible for >15% of AIDS-related deaths. A recent study by Xu et al. showed that Batf3-dependent conventional type 1 dendritic (cDC1) cells are key players in generating IFNγ+ CD4+ T cell and fungicidal lung and brain tissue-resident responses during murine cryptococcosis, contributing to fungal clearance in the lungs and brain of mice (J. Xu, R. Hissong, R. Bareis, A. Creech, et al., mBio 15:e02853-23, 2024, https://doi.org/10.1128/mbio.02853-23). However, despite their critical role, the depletion of Batf3-dependent cDC1 cells did not significantly alter overall mouse survival or disease progression, highlighting the complex immune regulation required to survive cryptococcal infection and the need for further research in medical mycology.